Using the EU-SILC to model the impact of the economic crisis on inequality - Cathal O'Donoghue; Jason Loughrey; Karyn Morrissey (IZA Journal of European Labor Studies, 2013)
In this paper we attempted to chart the impact of the early part of Ireland's economic crisis from 2008-2009 on the distribution of income. In order to decompose the impact of changes in different income components, we utilised a microsimulation methodology and the EU-SILC User Database. This simulation based methodology involved the disaggregation of the 6 main benefit variables in the EU-SILC into 17 variables for our tax-benefit model. Validating, our results were positive, giving us confidence in our methodology. We utilised the framework to model changes in the level of income inequality from the period just before the crisis in 2004 to the depth of the worst year of the crisis in 2009. In terms of the impact of the economic crisis, we found that income inequality fell in the early part of the crisis modelled in this paper. Much of this change was due to rising inequality of market incomes, (even when discounting unemployment). This was due to the differential effect of the downturn on different sectors where some sectors such as the construction and public sectors were significantly hit, while the international traded sectors have been relatively immune from the downturn and have seen continued growth. The impact of the tax-benefit system has been to mitigate this upward pressure, with a gradual rise in the redistributive effect of the tax-benefit system driven by an increase in demand on the benefits side and increased progressivity on the tax side.
Keywords: H22; H55; C15; 330; Economic crisis; Inequality; Microsimulation modelling